PENGARUH ALAT PERAGA GEOBOARD DAN KEMAMPUAN DISPOSISI MATEMATIS TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS VII - Br Ginting, Aliya Monika; Haji, Saleh; Sumardi, Hari (LPPM Universitas Bina Bangsa, 2024)
This research aims to determine 1) differences in creative thinking abilities between students who use geoboard teaching tools and students who use conventional ones in class VII, 2) differences in creative thinking abilities between students with high disposition ability and low disposition ability in class VII, 3 ) the interaction of geoboard teaching tools and mathematical disposition abilities on students' creative thinking abilities in class VII. This type of research is quasi-experimental research. Data collection techniques in this research are test and non-test techniques. The data analysis technique in this research uses a two-way ANOVA technique. The research results obtained from testing the hypothesis for each formulation are 1) there is a difference in creative thinking ability between students who use geoboard tools and students who use conventional in class VII with a significant value <0.001, 2) there is a difference in creative thinking ability between students high disposition ability with low disposition ability in class VII with a significant value of 0.020, 3) there is an interaction between geoboard teaching tools and mathematical disposition ability on the creative thinking ability of students in class VII with a significant value <0.001